Learning Motivation Levels of Indigenous Papuan Students - Febi Adriana Mutiara Sogalrey; Meylani Aljeinie Tijow; Yan Dirk Wabiser; Richardo Fernandez; Anike N. Bowaire (Journal of Innovation in Educational and Cultural Research, 2025)
This study aims to determine the learning motivation level of indigenous Papuan students at Universitas Cenderawasih, Faculty of Teacher Training and Education. Using the Explanatory Sequential Design model, a mixed-methods approach was employed, combining quantitative and qualitative methods sequentially. A sample of 118 FKIP students was randomly selected from each study program, including indigenous Papuan students and students from other regions. We analyzed the data using descriptive statistical techniques and obtained qualitative data through interviews. The results indicated that students' learning motivation was influenced by two main factors: intrinsic motivation, which was found to be high, reflected in students' intrinsic motivation to learn, a sense of personal responsibility, and satisfaction when mastering complex material. Extrinsic motivation also played a role, though at a moderate level. Extrinsic factors such as family support, lecturers, and the desire to make parents proud were key motivators for academic achievement. This study contributes to understanding the motivational dynamics of indigenous Papuan students and offers insights for developing more effective and culturally sensitive educational policies and strategies.